PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA BRO & SIS CAFE KOTA BENGKULU - Sahputra, Sindi; Ekowati, Sri (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
The research objective was to determine the effect of location and promotion on purchasing decisions at Bro & Sis Cafe Bengkulu City. This type of research is quantitative research, data collection method is done by using a questionnaire. The sample in this study was 130 samples, which were considered sufficient to represent the population. The samples taken are consumers of Bro & Sis Cafe Bengkulu City. The data analysis used is multiple linear regression test, determination test and hypothesis test. The results showed that location has a positive effect on purchasing decisions at Bro & Sis Cafe Bengkulu City, meaning that if the location increases, the purchasing decision will also increase. The location of the Bengkulu City Bro & Sis Cafe which is in the campus environment can increase consumer decisions to shop at the Bengkulu City Bro & Sis Cafe. Promotion has a positive effect on purchasing decisions at Bro & Sis Cafe Bengkulu City, meaning that the more promotions increase, the purchasing decisions will also increase. Promotions carried out by Bro & Sis Cafe Bengkulu City on social media can attract consumers to come to Bro & Sis Cafe Bengkulu City. Location (X_1) and Promotion (X_2) together influence the purchasing decision (Y) of products at Bro & Sis Cafe Bengkulu City. Keywords: Location, Promotion, Purchase Decision